Sejarah Dan Dinamika Pemikiran Dalam Muhammadiyah - Noor Hasyim; Ismartono Balango; Wahid Rahmat Hidayat; M. Amin (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Muhammadiyah, as the largest modernist Islamic movement in Indonesia, has a long history marked by the dialectics of thought between purification and renewal. This article discusses the history of the birth of the Muhammadiyah Islamic organization in Indonesia and the dynamics of thought that developed within it from the early 20th century to the 21st century. The focus of the study includes the progressive Islamic ideology carried by the founders of Muhammadiyah, changes in thought in facing internal and external challenges, and the contributions of Muhammadiyah to the development of intellectual and social aspects of Muslims in Indonesia. This study uses a historical-qualitative approach with literature analysis and primary organizational sources, and evaluates the dynamics of thought based on the latest articles and scientific journals. The research findings show that Muhammadiyah's thought has continued to evolve from purifying Islamic teachings towards modernizing education, social, and responding to contemporary challenges, making Muhammadiyah a moderate, progressive, and socially relevant Islamic organization. Keywords: Muhammadiyah, Modernist Islamic Movement, Islamic Purification, Islamic Renewal Abstrak: Muhammadiyah sebagai gerakan Islam modernis terbesar di Indonesia memiliki sejarah panjang yang diwarnai oleh dialektika pemikiran antara pemurnian (purifikasi) dan pembaruan (dinamisasi). Artikel ini membahas sejarah lahirnya organisasi Islam Muhammadiyah di Indonesia dan dinamika pemikiran yang berkembang di dalamnya sejak awal abad ke-20 hingga abad ke-21. Fokus kajian meliputi ideologi Islam Berkemajuan yang diusung pendiri Muhammadiyah, perubahan pemikiran dalam menghadapi tantangan internal dan eksternal, serta kontribusi Muhammadiyah terhadap perkembangan intelektual dan sosial umat Islam di Indonesia. Kajian ini menggunakan pendekatan historis-kualitatif dengan analisis literatur dan sumber primer organisasi, serta mengevaluasi dinamika pemikiran berdasarkan artikel dan jurnal ilmiah terbaru. Hasil penelitian menunjukkan bahwa pemikiran Muhammadiyah terus berkembang dari purifikasi ajaran Islam ke arah modernisasi pendidikan, sosial, dan respon terhadap tantangan kontemporer, menjadikan Muhammadiyah sebagai organisasi Islam yang moderat, progresif, dan relevan secara sosial. Kata Kunci: Muhammadiyah, Gerakan Islam Modernis, Pemurnian Islam, Pembaruan Islam